Constitutionalism: Rule Of Law And Human Rights Protection In The Philippines - Suharsono, Agus (Jurnal Transformasi Administrasi, 2025)
This paper examines the implementation of the principle of constitutionalism in the Philippines based on the 1987 Constitution, focusing on two key dimensions of the Rule of Law Index: constraints on government powers and the protection of human rights. Although the Philippine Constitution normatively provides a comprehensive framework for the rule of law and guarantees fundamental rights, its implementation continues to face serious challenges. The country’s average Rule of Law Index score over the past decade reflects weak accountability, limited judicial independence, and inadequate protection for vulnerable groups. This study employs a normative juridical method with constitutional and conceptual approaches, and recommends strengthening oversight institutions, reforming the judicial system, enhancing civil society participation, and fostering a culture of legal ethics as strategic steps to reinforce the rule of law substantively.